(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
In this paper, several issues are discussed concerning the Basque language in Late Antiquity. It is argued that, in today’s Basque provinces, Basque was not spoken in the High Empire period, thus disagreeing with some interpretations which postulate a Bascoid substrate previous to any Indo-European layer. To that end, in Section 2, some chronological arguments based on modern toponymy are put forward, and, in Section 3, an analysis is made of all the toponymic, anthroponymic and theonymic data contained in the sources of Antiquity. In Section 4, an explanation is proposed as to who were the speakers of Old Common Basque in the 5th-6th centuries, as well as to when and how Basque penetrated from the Pamplona Basin into the Alavese Plain, in view of the earliest dialectal evidence and the most recent archaeological finds.